A new reading of Spencer on 'society', 'organicism' and 'spontaneous order'. (November 2015) - Offer, John
Herbert Spencer represented societies as 'social organisms', but he also interpreted social life as a 'spontaneous order'. This new reading of Spencer argues that these positions are not incompatible. The sociological challenge he tackled was how to conceptualise order, pattern and change in the mutually interdependent lives of social individuals as moral beings. Many critics, including Tönnies, Durkheim and Bosanquet, overlooked the subtlety of Spencer's thought on the social organism and socially minded individuals, including its focus on 'transcendental physiology' and morphological variety. As a legacy, we behold mythical accounts of Spencer, either as an exponent of a reified 'social system' or as a mouthpiece for 'laissez-faire', and amoral 'individualism'. This article suggests that individuals were understood to be neither 'atomic' nor amoral but capable of altruism and beneficence and to exhibit a 'social self-consciousness' within societies whose structures were mutable. If correct, Spencer's contribution to the history of sociology has been commonly misjudged, and his basic thought retains value for sociology today in respect of ideas of individualism, holism and 'society'.